CHARACTERIZATION OF SAPROPHAGE INSECTS FORENSIC ENTOMOLOGY INDICATORS USING LOCAL PIGS - Kandowangko, Sandy; Wurarah, Masje; Mokosuli, Yermia; Satiman, Utari; Gedoan, Sukmarayu (Universitas Negeri Manado, 2024)
Forensic entomology is the science of insects which is used to analyze cases related to forensics, namely death. This is based on the close relationship between humans and insects who live side by side. Insects can be a factor in determining the Postmortem Interval (PMI) so that it is useful in the forensic investigation process. Medicolegal insects are insects that are used as evidence in death cases. This research aims to obtain the diversity of insect species, the morphological characteristics of insects, the characteristics of insects in experimental pigs that died from hanging, poisoning and stabbing and based on the stage of decomposition. The results of this research examine temperature, soil pH, air humidity and the decomposition process of local pigs. The results of research on the decomposition stage in 3 deaths (hanging, stabbing, and poisoning) showed differences in the time of death, where the hanging carcass decomposed more quickly than the stabbed and poisoned carcass. In the decomposition stage, the first insect encountered is the order (Diptera) where these insects damage internal organs such as the brain and liver and also damage body cells. The temperature results of local pig carcasses placed outdoors ranged from 32.2-34.50C, while indoor carcass temperatures ranged from 26.77-33.43 0C. The degree of acidity (pH) of carcasses placed outdoors ranges from 5.13-8.53 while indoor carcasses ranges from 6.0-7.77. The environmental temperature of animal bodies placed outdoors ranges from 26.35-39,740C, while humidity ranges from 57.79-86.10%. The temperature of animal bodies in the room ranges from 27.54-31,520C, while humidity ranges from 71.50-85.37%.